Aspirin Therapy for Primary Prevention: The Case for Continuing Prescribing to Patients at High Cardiovascular Risk—A Review - De Caterina, Raffaele; Aimo, Alberto; Ridker, Paul M. (Thrombosis and Haemostasis, 2020)
Current evidence supports the use of low-dose aspirin for secondary cardiovascular prevention. By contrast, the benefit-to-risk ratio of aspirin use in primary prevention is debated: three contemporary randomized control trials have been conflicting, and meta-analyses have concluded for an unclear clinical benefit, based on the consideration that the reduction in thromboembolic events is counterbalanced by increased bleeding. The primary prevention setting is, however, a heterogeneous mix of subjects at highly variable cardiovascular risk. One possible explanation for the uncertainty of data interpretation is the progressive reduction in risk of major adverse cardiovascular events (MACEs) in primary prevention that has accompanied global education programs, leading patients to smoke less, exercise more, and increasingly take lipid-lowering therapies. Based on a meta-regression of the benefits and harm of aspirin therapy in primary prevention as a function of the 10-year risk of MACE, we favor a nuanced approach still, however, based on the evaluation of cardiovascular risk, acknowledging differences between patients and emphasizing an individualized assessment of both benefits and harm. After optimal control of cardiovascular risk factors, and when patients are less than 70 years of age, clinicians should assess the risk of MACE and base decision on such stratification, considering the risk of bleeding and patient preferences. Clinicians would then advise the use of aspirin in primary prevention patients at the highest risk of MACE who do not have a prohibitive risk of bleeding, and in the majority of cases after initiation of properly titrated statin therapy.
Keywords: aspirin; primary cardiovascular prevention; bleeding; major acute cardiovascular events; MACE; benefit–risk balance